Novel Insulin-Like Growth Factor 1 Gene Mutation: Broadening of the Phenotype and Implications for Insulin Resistance - Giacomozzi, Claudio; Martin, Ayelen; Fernández, María Celia; Gutiérrez, Mariana; Iascone, Maria; Domené, Horacio M; Dominici, Fernando P; Bergadá, Ignacio; Cangiano, Biagio; Persani, Luca; Pennisi, Patricia A (The journal of clinical endocrinology and metabolism, 2023)
Abstract Context Insulin-like growth factor (IGF)1 gene mutations are extremely rare causes of pre- and postnatal growth retardation. Phenotype can be heterogenous with varying degrees of neurosensory deafness, cognitive defects, glucose metabolism impairment and short stature. Objective This study describes a 12.6-year-old girl presenting with severe short stature and insulin resistance, but with normal hearing and neurological development at the lower limit of normal. Methods DNA was obtained from the proband and both parents for whole exome sequencing (WES). In silico analysis was performed to predict the impact of the IGF1 variant on IGF1 and insulin receptors (IGF1R and IR) signaling. Phosphorylation of the IGF1R at activating Tyr residues and cell proliferation analyses were used to assess the ability of each subject's IGF1 to bind and activate IGF1R. Results The proband had low immunoreactive IGF1 in serum and WES revealed a novel homozygous IGF1 missense variant (c.247A>T), causing a change of serine 83 for cysteine (p.Ser83Cys; p.Ser35Cys in mature peptide). The proband's parents were heterozygous for this mutation. In silico analyses indicated the pathogenic potential of the variant with electrostatic variations with the potential of hampering the interaction with the IGF1R but strengthening the binding to IR. The mutant IGF1 protein had a significantly reduced activity on in vitro bioassays. Conclusion We describe a novel IGF1 mutation leading to severe loss of circulating IGF1 immunoreactivity and bioactivity. In silico modeling predicts that the mutant IGF1 could interfere with IR signaling, providing a possible explanation for the severe insulin resistance observed in the patient. The absence of significant hearing and neurodevelopmental involvement in the present case is unusual and broadens the clinical spectrum of IGF1 mutations.